Edukasi Perubahan Psikologi dalam masa Kehamilan Di Wilayah Kerja Puskesmas Jumpandang Baru - Haryati Sahrir; A Yantimala; Baktiar Baktiar; Rosna Idi (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2021)
Pregnancy is a physiological and normal process, not only related to biological aspects but also related to a woman's psychological, emotional and spiritual aspects in life. A woman has a duty to fulfill the role of a mother during her pregnancy. This service activity is carried out with the aim of providing information about pregnancy, various psychological changes during pregnancy and how to make psychological adaptations during pregnancy in achieving the role of mother at the Jumpandang Baru Community Health Center. The number of participants in this service activity was 20 people which was carried out on November 21 2020 at the Tallo District Office using the lecture and question and answer method as well as the sharing method. The results of this activity show changes in behavior in the form of successful adaptation, especially in psychological changes during pregnancy.